2020
DOI: 10.1101/2020.03.05.978684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model-based design and analysis of life table experiments for insect vectors

Abstract: AbstractLife tables help identify physiological differences in distinct development stages and detect potential vulnerabilities for conservation and control. However, cataloguing mortality, development, and fecundity by following each individual could be challenging in insects due to interweaving generations and development stages.Here, we propose to use age- and stage-structured population dynamics modelling to help derive life table characteristics from the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It is also essential to further study the link between the observed egg/larval stages numbers and female numbers throughout the season such as the study conducted by Manica et al (2017). Finally, detailed and pivotal data on key life-history traits, such as survival and development, are only available from laboratory experiments but parameters derived solely from such datasets cannot be extrapolated to larger areas (Erguler et al, 2020). Research networks such as VectorBite (Shocket et al, 2019) try to collate these life traits, but currently these databases are still in the setup phase and cannot be used as such.…”
Section: Articlementioning
confidence: 99%
“…It is also essential to further study the link between the observed egg/larval stages numbers and female numbers throughout the season such as the study conducted by Manica et al (2017). Finally, detailed and pivotal data on key life-history traits, such as survival and development, are only available from laboratory experiments but parameters derived solely from such datasets cannot be extrapolated to larger areas (Erguler et al, 2020). Research networks such as VectorBite (Shocket et al, 2019) try to collate these life traits, but currently these databases are still in the setup phase and cannot be used as such.…”
Section: Articlementioning
confidence: 99%